Factors that influencing job performance among the MPSPK staff / Nurul Fawzia Hanis Jailani and Rafidah Ramli - Jailani, Nurul Fawzia Hanis; Ramli, Rafidah (2019)
This paper review the extent of job performance of the Majlis Perbandaran Sungai Petani Kedah (MPSPK) staff and the factors that influenced the job performance of the staff. Job performance of the staff is important in determining the organizational outcomes. Local authorities’ staff in Malaysia possess different extent of job performance thus this study is important to know the extent of job performance among the MPSPK staff. The factors that influenced the job performance of MPSPK staff is important to be known as this finding will help the future researcher. Besides, the finding of this study also give a knowledge for the organization in a way to boost the job performance of the staff. This study used salary, work stress, work environment and motivation as the independent variables and job performance of MPSPK staff as the dependent variables. This study used group C staff as the sample size and quantitative method is used as the examination technique. The reliable findings concluded that the job performance of the MPSPK staff is at the good extent.